Non-Thermal Plasma Jet-Treated Medium Induces Selective Cytotoxicity against Mycobacterium tuberculosis-Infected Macrophages - Chae Bok Lee; Kang In Lee; Young Jae Kim; In Taek Jang; Sintayehu Kebede Gurmessa; Eun Ha Choi; Nagendra Kumar Kaushik; Hwa-Jung Kim (Biomedicines, 2022)
Plasma-treated media (PTM) serve as an adjuvant therapy to postoperatively remove residual cancerous lesions. We speculated that PTM could selectively kill cells infected with Mycobacterium tuberculosis (Mtb) and remove postoperative residual tuberculous lesions. We therefore investigated the effects of a medium exposed to a non-thermal plasma jet on the suppression of intracellular Mtb replication, cell death, signaling, and selectivity. We propose that PTM elevates the levels of the detoxifying enzymes, glutathione peroxidase, catalase, and ataxia-telangiectasia mutated serine/threonine kinase and increases intracellular reactive oxygen species production in Mtb-infected cells. The bacterial load was significantly decreased in spleen and lung tissues and single-cell suspensions from mice intraperitoneally injected with PTM compared with saline and untreated medium. Therefore, PTM has the potential as a novel treatment that can eliminate residual Mtb-infected cells after infected tissues are surgically resected.